Arts of living : reinventing the humanities for the twenty-first century - Spellmeyer, Kurt. (Albany : State University of New York Press, 2003)
"Arts of Living presents a social history of the humanities and a proposal for the future that places creativity at the heart of higher education. Engaging with the debate launched by Allan Bloom, Harold Bloom, Bill Readings, John Guillory, and others, Kurt Spellmeyer argues that higher education needs to abandon the "culture wars" if it hopes to address the major crises of the century: globalization, the degradation of the environment, the widening chasm between rich and poor, and the clash of cultures."--Jacket
Machine generated contents note: 1. Taking the Humanities Out of the Box -- 2. Democracy Sets in the West : From Able Citizens to Ignorant Masses -- 3. Great Divide: The Professions Against Civil Society -- 4. Trouble with English: The Rise of the Professional Humanities and Their Abandonment of Civil Society -- 5. Poverty of Progress: James Agee, Lionel Trilling, and the Alienation of Knowledge -- 6. Wages of Theory: Isolation and Knowledge in the Humanities -- 7. World without End: Criticism or Creation in the Humanities? -- 8. Specialists with Spirit: The Humanities -- Outside the University -- 9. "Art Serves Love": The Arts As a Paradigm for the Humanities -- 10. Travels to the Heart of the Forest: Dilettantes and Professionals in the Twentieth Century -- Postscript: Could Teaching, of All Things, Prove to Be Our Salvation?
Includes bibliographical references (pages 249-296) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Humanities -- Study and teaching (Higher) -- United States; Humanities -- Philosophy; Learning and scholarship -- United States -- History; Humanities -- Political aspects -- United States; Humanities -- United States -- History; Savoir et érudition -- États-Unis -- Histoire; REFERENCE -- Questions & Answers; Humanities; Humanities -- Philosophy; Humanities -- Political aspects; Humanities -- Study and teaching (Higher); Learning and scholarship; United States; History